HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU IBU RUMAH TANGGA TERKAIT PEMERIKSAAN PAYUDARA KLINIS (SADANIS) DI WILAYAH KERJA PUSKESMAS KUTA SELATAN SAAT PANDEMI COVID-19 - Artha Sari, Ni Putu Yunik; Subrata, I Made (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022DO - 10.24843/ACH.2022.v09.i03.p07, 2022)
ABSTRACT The high prevalence of breast cancer cases in Indonesia is due to delays in checking themselves for the first time to health services, so that breast cancer cases are more often found at an advanced stage. The reason is the lack of early detection behavior of CBE. This behavior can be influenced by several factors, namely the level of knowledge and attitudes. The purpose of this research was to determine the relationship between the level of knowledge and attitudes with the behavior of housewives related to CBE in the work area of the South Kuta Health Center during the Covid-19 pandemic. The research used a cross-sectional design with 167 samples selected by multi-stage random sampling. The data was collected using a questionnaire and analyzed using the chi-square test. The results showed that most of the housewives did not perform early detection of breast cancer with CBE of 82,04%. There is a significant relationship between attitudes and behavior of householders related to CBE (p = 0,010; OR = 2,91; 95% CI = 1,29-6,56). Meanwhile, knowledge did not have a significant relationship with the behavior of housewives related to CBE in the Work Area of the South Kuta Health Center during the Covid-19 pandemic (p value = 0,796; OR = 1,32; 95%CI = 0.15-11,45). It is necessary to improve old programs, form cadres and refresh trained personnel both in terms of examinations and strengthen health promotion in an effort to increase the coverage of early detection with CBE. Keywords: CBE, Behavior, Housewife